Tolerancia y prácticas educativas actuales - Colom Cañellas, Antonio J. (Revista Española de Pedagogía, 2018)
The paper presents a conceptual and educative tolerance's model based on the cognitive theory. Tolerance focuses the current educative practices, as much in formal education (environmental and intercultural education) as in not formal education (tourism and the not governmental organisations). In order to show that new educative perspectives are valuable for tolerance development.
Keywords: tolerancia; prácticas educativas; educación actual; Revista Española de Pedagogía